Preparation of poly(N-vinylpyrrolidone)-stabilized ZnO colloid nanoparticles - Gutul, Tatyana; Rusu, Emil; Condur, Nadejda; Ursaki, Veaceslav; Goncearenco, Evgenii; Vlazan, Paulina (Beilstein Journal of Nanotechnology, 2014)
We propose a method for the synthesis of a colloidal ZnO solution with poly(N-vinylpyrrolidone) (PVP) as stabilizer. Stable colloidal solutions with good luminescence properties are obtained by using PVP as stabilizer in the synthesis of ZnO nanoparticles by a sol–gel method assisted by ultrasound. Nanoparticles with sizes of 30–40 nm in a PVP matrix are produced as a solid product. The colloidal ZnO/PVP/methanol solution, apart from the most intense PL band at 356 nm coming from the PVP, exhibits a strong PL band at 376 nm (3.30 eV) which corresponds to the emission of the free exciton recombination in ZnO nanoparticles.
Keywords: colloidal solutions; nanocomposite; poly(N-vinylpyrrolidone); sol–gel; zinc oxide